Motor–Cognitive Treadmill Training With Virtual Reality in Parkinson’s Disease: The Effect of Training Duration - Pelosin, Elisa; Ponte, Chiara; Putzolu, Martina; Lagravinese, Giovanna; Hausdorff, Jeffrey M.; Nieuwboer, Alice; Ginis, Pieter; Rochester, Lynn; Alcock, Lisa; Bloem, Bastiaan R.; Nieuwhof, Freek; Cereatti, Andrea; et al. (Frontiers in Aging Neuroscience, 2022)
Treadmill training with virtual reality (TT+VR) has shown to improve gait performance and to reduce falls risk in Parkinson’s disease (PD). However, there is no consensus on the optimal training duration. The present study is a sub-study of the VTIME randomized clinical trial (NCT01732653). Here we explored the effect of the duration of a training based on motor-cognitive interaction on motor and cognitive performance and on falls risk in PD subjects. Patients in Hoehn & Yahr stage 2-3, age between 40 and 70 years were included. Ninety-six patients with PD were assigned to 6-weeks or 12-weeks of TT+VR intervention and 77 patients completed the full protocol. Outcome measures for gait and cognitive performance were assessed at baseline, immediately after training and at 1 month and 6 months follow-up. Incident rate of falls in the 6-months pre intervention was compared to that in the 6-months post intervention. Dual task gait performance (gait speed, gait speed variability and stride length under cognitive dual task and obstacle negotiation and the leading foot clearance in obstacle negotiation) improved similarly in both groups with gains sustained at 6-months follow-up. Higher decrease in fall rate and fear of falling were observed in participants assigned to the 12-weeks than the 6-weeks intervention. Improvements in cognitive functions (executive functions, visuo-spatial ability and attention) were seen only in participants enrolled in 12-weeks training up to 1-month follow-up, but vanished at the 6 months evaluation. Our results suggest that a longer TT+VR training leads to greater improvements in cognitive functions especially those directly addressed by the virtual environment.